Medicinal Chemistry Strategies to Disrupt the p53–MDM2/MDMX Interaction - Lemos A. (2016)
The growth inhibitory activity of p53 tumor suppressor is tightly regulated by interaction with two negative regulatory proteins, murine double minute 2 (MDM2) and X (MDMX), which are overexpressed in about half of all human tumors. The elucidation of crystallographic structures of MDM2/MDMX complexes with p53 has been pivotal for the identification of several classes of inhibitors of the p53–MDM2/MDMX interaction. The present review provides in silico strategies and screening approaches used in drug discovery as well as an overview of the most relevant classes of small-molecule inhibitors of the p53–MDM2/MDMX interaction, their progress in pipeline, and highlights particularities of each class of inhibitors. Most of the progress made with high-throughput screening has led to the development of inhibitors belonging to the cis-imidazoline, piperidinone, and spiro-oxindole series. However, novel potent and selective classes of inhibitors of the p53–MDM2 interaction with promising antitumor activity are emerging. Even with the discovery of the 3D structure of complex p53–MDMX, only two small molecules were reported as selective p53–MDMX antagonists, WK298 and SJ-172550. Dual inhibition of the p53–MDM2/MDMX interaction has shown to be an alternative approach since it results in full activation of the p53-dependent pathway. The knowledge of structural requirements crucial to the development of small-molecule inhibitors of the p53–MDMs interactions has enabled the identification of novel antitumor agents with improved in vivo efficacy. © 2016 Wiley Periodicals,